The Maqasidi dimension and its impact in shaping legal fatwa: Al-Misyar marriage as a case study - Bouheraoua, Said (IIUM Press, 2009)
This research examines the issue of Al-Misyar marriage from a Maqasidi dimension and to appreciate its contribution to a more comprehensive, rational and realistic fatwa on the issue. The research enhances the awareness of the Maqasid approach in producing fatwas on the contemporary issues. The objectives of the research are: first, to identify the methods of Maqasid in this issue; second, to explain how the Maqasidi dimension may contribute to a more comprehensive, rational and realistic fatwas; third, to enhance awareness of the utility of Maqasid in producing fatwas on the contemporary issues.